Assessment of antioxidant capacity and liquid chromatography-mass spectrometry chemical profiling in MRQ74 and MRQ76 rice varieties - Ridzwan, Norhaslinda; Khalili Rohin, Mohd Adzim; Abd Hadi, Norhayati; Abu Bakar, Mohd Fadzelly; Saad, Norazlina; Ishak, Ruziana (Open Science Publishers LLP Inc., 2025)
Rice is a common, nutritious grain that is widely consumed globally as a staple food. The purpose of this study was to comparatively analyze a new variety of fragrant rice in Malaysia, MRQ74 and MRQ76: fresh polished; unpolished, and 3-month-aged polished; unpolished using total phenolic content (TPC), total flavonoid content (TFC), antioxidant assay, and liquid chromatography-mass spectrometry (LC-MS) chemical profiling. In this study, the Paddy and Rice Research Centre, Malaysian Agricultural Research and Development Institute, Seberang Perai, Pulau Pinang, provided the new cultivars of fragrant rice varieties, MRQ74 and MRQ76. The TPC and TFC assays were performed using a Folin Ciocalteu’s reagent and an aluminum chloride colorimetric technique, respectively. The antioxidant activity was measured using the Ferric Reducing Antioxidant Power colorimetric test kit from Abcam, China. Chemical profiling was carried out by the Integrative Pharmacogenomics Institute, Universiti Teknologi Mara, Selangor by utilizing a LC-MS system equipped with an Agilent 1200 liquid chromatography system. Each rice variety sample had extractable TPC, TFC, and antioxidant content, with 76 FUP having the greatest phenolic value (261.35 ± 0.01 mg GAE/100 g), and 76 FP having the highest antioxidant (0.37 ± 0.01 mM ferrous equivalent) and flavonoid value (1715.00 ± 0.01 mg CE/100 g). Based on the chromatography analysis data, 48 compounds with Db scores ranging from 90% to 100% were identified as minor organic acids, amino acids, vitamins, flavonoid derivatives, and phenolic acids. As a result, the data were able to highlight the health-benefits worth of the MRQ74 and MRQ76 rice types, allowing for improved future exposure to consumers.